2018
DOI: 10.1002/cche.10028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growing location and variety on nutritional and functional properties of proso millet (Panicum miliaceum) grown as a double crop

Abstract: Background and objectives Despite positive agronomic and nutritional characteristics, millets are underutilized for food use in the Western Hemisphere. Little is known about the end‐use quality characteristics of available proso millet varieties, nor their adaptation to and performance in double crop situations in northern states. Therefore, the objective of this work was to evaluate several proso millet varieties grown in two locations for composition as well as attributes that influence processing, nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 75 publications
3
28
0
Order By: Relevance
“…Lutein content in HRW is within previously reported range (Moore et al ., ; Hidalgo et al ., ; Abdel‐Aal et al ., ; Ndolo & Beta, ). The carotenoid content of IWG samples is within the range (7–8 μg g −1 lutein; 0.5–0.94 μg g −1 zeaxanthin) reported for einkorn (Hidalgo et al ., ; Abdel‐Aal et al ., ) and similar to proso millet (8.1–17.1 μg lutein g −1 ; 1.2–2.4 μg zeaxanthin g −1 ) (Tyl et al ., ). For some IWG samples, lutein was in the range of levels found in corn (21.9 μg lutein g −1 ) (Abdel‐Aal et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Lutein content in HRW is within previously reported range (Moore et al ., ; Hidalgo et al ., ; Abdel‐Aal et al ., ; Ndolo & Beta, ). The carotenoid content of IWG samples is within the range (7–8 μg g −1 lutein; 0.5–0.94 μg g −1 zeaxanthin) reported for einkorn (Hidalgo et al ., ; Abdel‐Aal et al ., ) and similar to proso millet (8.1–17.1 μg lutein g −1 ; 1.2–2.4 μg zeaxanthin g −1 ) (Tyl et al ., ). For some IWG samples, lutein was in the range of levels found in corn (21.9 μg lutein g −1 ) (Abdel‐Aal et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The gradient profile was adapted from Dobberstein & Bunzel (), as modified by Tyl et al . (). External standard curves were constructed for quantification.…”
Section: Methodsmentioning
confidence: 97%
“…Protein content was determined following AACCI Dumas combustion method 46-30.01, using 6.25 as the protein conversion factor. Carotenoids in raw and cooked pasta were analyzed in triplicate with highperformance liquid chromatography as described by Tyl et al (2018), without modification.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…A concerted effort along the production chain, from farmer to consumer, is needed to promote millet-based foods. In a previous study, we evaluated Minnesota-grown proso millet (Panicum miliaceum) for compositional, nutritional and functional characteristics (Tyl, Marti, Hayek, Anderson, & Ismail, 2018). Distinct differences among varieties included amylose to amylopectin ratio and carotenoid content (Tyl et al, 2018) which have been shown to influence pasta quality , Marti, D'Egidio, & Pagani, 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation